A new QTL for plant height in barley (Hordeum vulgare L.) showing no negative effects on grain yield. - Junmei Wang; Jianming Yang; Qiaojun Jia; Jinghuan Zhu; Yi Shang; Wei Hua; Meixue Zhou (PLoS ONE)
Introduction Reducing plant height has played an important role in improving crop yields. The success of a breeding program relies on the source of dwarfing genes. For a dwarfing or semi-dwarfing gene to be successfully used in a breeding program, the gene should have minimal negative effects on yield and perform consistently in different environments. Methods In this study, 182 doubled haploid lines, generated from a cross between TX9425 and Naso Nijo, were grown in six different environments to identify quantitative trait loci (QTL) controlling plant height and investigate QTL × environments interaction. Results A QTL for plant was identified on 7H. This QTL showed no significant effects on other agronomic traits and yield components and consistently expressed in the six environments. A sufficient allelic effect makes it possible for this QTL to be successfully used in breeding programs.